Early detection of the orchid flowering gene PaFT1 in tobacco cells using a GFP reporter - Sri Wahyuningsih; Muhammad Dylan Lawrie; Budi Setiadi Daryono; Sukarti Moeljopawiro; Soenghoe Jang; Endang Semiarti (Indonesian Journal of Biotechnology, 2016)
Here we describe a novel method of using green fluorescence protein (GFP) as a reporter gene for early detection of an integrated TDNA containing the orchid flowering gene, PaFT1 (Phalaenopsis aphrodite Flowering locus T1) in the tobacco genome. Functional assays that report the presence of exogenous DNA early in development are especially useful in plants where the desired phenotype is only apparent after long periods of vegetative growth. The objective of this study is to establish a method for detecting an inserted Phalaenopsis orchid flowering gene and examining its function in tobacco. The p35S::PaFT1 35S::GFP construct was introduced into Agrobacterium tumefaciens strain EHA101. Transformed tobacco leaves were cultured on MS medium with addition of 1 mgL-1 NAA+3 mgL-1 BAP+50 mgL-1 Kanamycin+300 mgL-1 timentin for selection. Results showed bright green GFP fluorescent signals in 11 out of 15 (73%) tobacco leaf cells at a 2month time point after transformation. GFP and PaFT1 fragments were amplified in genomic PCR using GFP and PaFT1 specific primers. The accumulated PaFT1 transcripts were observed in 3 monthold transgenic tobacco plants containing p35S::PaFT135S::GFP. Green florescence was observed only in the transgenic plants at the 5 monthold stage but not in the wild type controls.